DEVELOPING AND IMPLEMENTING A HANGMAN GAME FOR HSK TEST TAKERS WITH FLUTTER - Yefta Christian; Denissa Denissa (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Mandarin Chinese, or more commonly known as Modern Chinese, is one of the worlds’ many languages. It is the main official language of the People’s Republic of China, and it is also one of the most anticipated languages across the world. In year 2020, the Mandarin language is the second most spoken language in the world at 1.12 billion speakers (Caplan, 2020). To facilitate the growing use of Mandarin in workplace, more and more private schools are teaching Mandarin as a second language. This leads to a need to assess the expertise of the speakers, which leads to the creation of certain Chinese proficiency test such as Hanyu Shuiping Kaoshi (HSK). To support HSK test takers, the author intends to provide a new kind of media to help the test takers expand their vocabulary. With the help of Flutter and Firebase Cloud Firestore, the result is an e-learning mobile application, served as a hangman game. Survey results shows people are interested in the application and believed that it can help the players expand their vocabularies.